Oculomotor Synkinesis Secondary to Meningocele: Report of a Rare Case - Benjamin Walker; Krishnakumari A. Modi; Leonardo F. Freitas; Nitesh Shekhrajka (Indian Journal of Radiology and Imaging)
Oculomotor synkinesis or aberrant regeneration of cranial nerve III (CN III) typically results from trauma, aneurysm, or mass lesions. We present a rare case report with CN III palsy and synkinesis secondary to a meningocele in the left oculomotor cistern, causing mass effect on the oculomotor nerve. Imaging suggested underlying idiopathic intracranial hypertension (IIH) as a potential etiology. While mass lesions or trauma are common causes of oculomotor synkinesis, an association with meningocele has not been previously reported. This case highlights the importance of considering IIH-related meningoceles in unexplained CN III palsies.